(untitled) (Journal of Social Sciences Review, 2024)
In Pakistan, the pursuit of freedom of expression encounters a complex landscape marked by aspirations for an open society and significant challenges and restrictions. This article explores the multifaceted dilemma of free speech in Pakistan, addressing the tensions between individual liberties, societal norms, political interests, and security concerns. Legal constraints, particularly blasphemy laws and defamation statutes, hinder free expression, while political dynamics, including authoritarian governance and the influence of religious extremism, exacerbate confrontations and restrictions. Journalists face threats and harassment, and the digital sphere is subject to increased censorship. Societal attitudes rooted in religious conservatism, honor culture, and patriarchal structures perpetuate self-censorship and conformity. Despite these challenges, voices of resistance persist, including civil society organizations and human rights activists advocating for pluralism and accountability. The research aims to analyze the legal, political, social, and cultural factors shaping the dilemma of free speech in Pakistan, highlighting the need to address root causes, foster dialogue, and promote tolerance for progress towards a more open and inclusive society.